Disposisi Matematis dan Self Efficacy Terhadap Hasil Belajar Matematika Siswa Kelas XI IPA SMAN 4 Wajo - Nurfadilah Mahmud; Sartika Arifin; Evi Muhtar (Griya Journal of Mathematics Education and Application, 2023)
This study aims to determine the effect of mathematical disposition and self-efficacy on mathematics learning outcomes for students of class XI IPA and IPA at SMAN 4 Wajo. The type of research used is ex-post facto research with a sample of 85 students from the population of class XI IPA and IPA at SMAN 4 Wajo, which were selected using the saturated sampling technique. The instrument used the following for data collection technique are questionnaire (a mathematical disposition and a self-efficacy) and a mathematics learning outcome test. Data analysis used descriptive and inferential statistical for hypothesis testing using simple linear regression analysis and multiple linear regression analysis. The results of the hypothesis test in this study indicate that: (1) there is a positive and significant effect of mathematical disposition on students’ mathematics learning outcomes, (2) there is a no positive and significant effect of self-efficacy on students’ mathematics learning outcomes, and (3) there is the positive and significant influence of mathematical disposition and self-efficacy together on students’ mathematics learning outcomes.